POWER GENERATION USING MAGLEV WIND TURBINE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Since a decade the demand for electricity is increasing rapidly and rate of power demand is running ahead of supply. The present day existing schemes of power generation are insufficient to keep pace with ever increasing demand. To overcome this problem we have to invent new schemes of power generation and acquire maximum renewable energy in efficient way. The recent severe energy crisis has forced to think & develop the power generation by renewable sources. This project dwells on the implementation of an alternate structure of a wind turbine for power generation purposes. Magnetic levitation has apparently moved to paradigm stage. The levitating blades spin with little resistance, and the power output is increased. They also can be a spin in light breezes. Maglev wind turbine principle provides efficient frictionless power generation with less maintenance, compared to Horizontal Axis Wind Turbine ordinary system. The aim of this major qualifying project is to design and implement a magnetically levitated wind turbine system that has the ability to operate in both low and high wind speed velocity conditions. This new model of wind turbine uses magnetic levitation to reduce the internal friction of the rotor which is considered as a revolution in the field of wind technology, and reduces the effect of gravitational force, producing 30% more energy than a conventional ordinary turbine, at the same time decreasing operational costs by 45% over the ordinary wind turbine.